Reaching the rural poor through agricultural cooperatives in Mongolia (Mongolian Journal of Agricultural Sciences, 2017)
The paper is preoccupied with the cooperative sector in central Mongolia. Its aim is to provide new insights into the role and importance of cooperatives in regard to poor rural populations. In the paper we analyze the inclusiveness of smaller herders and farmers with in the cooperatives. The research is based on data collection in selected provinces of the Tov region. The data were collected for three distinctive target groups-cooperative board members, cooperative members and non-members/herders. We found that the cooperative sector in Mongolia is strongly affected by the governmental policy of wool subsidies, which allows subsidies only to cooperative members, and is thus potentially leading to very low levels of members self-identification with the cooperative due to big increases in the numbers of new cooperative members. This policy is potentially also affecting the inner organizational structure of cooperatives. Further, we have found suggestions that poorer herdsmen tend not to be members of cooperatives and overall benefits for non-members and the general community arising from local cooperatives are rather low.